A series of lanthanide-organic frameworks based on 2-Propyl-1H-imidazole-4,5-dicarboxylate and oxalate: syntheses, structures, luminescence, and magnetic properties - Feng, X.; Zhao, J.; Liu, B.; Wang, L.; Ng, S.W.; Zhang, G.; Wang, J.; Shi, X.; Liu, Y. (American Chemical Society, 2011)
A family of self-assembly lanthanide-organic coordination polymers with both rigid and flexible ligands formulated as {[Ln(2)(Hpimda)(2)(mu(4)-C2O4)center dot 2H(2)O]center dot 4H(2)O}(n) (Ln = Sm (1), Eu (2), Tb (3), Dy (4), Ho (5), Er (6), H(3)pimda = 2-propyl-1H-imidazole-4,5-dicarboxylic acid) has been synthesized from the reactions of H3pimda with trivalent lanthanide salts in the presence of oxalate as coligand. X-ray diffraction analysis reveals that these complexes are isomorphous and isostructural, and each forms a novel three-dimensional (3D) frameworks structure, in which the metalloligands' two-dimensional (2D) networks were constructed from the lanthanide ion, 2-propyl-imidazole-dicarboxylate as well as oxalate ligands, and the oxalate further acts is a pillar to link the [Ln(Pimda)(oxo)] 2D grids to generate the 3D open frameworks, leaving one-dimensional channels. which are occupied by water clusters displaying an intricate array. The luminescence emission spectra of the complexes vary depending on which lanthanide ion is present. In addition, compounds 3, 4, and 5 exhibited weak but significant ferromagnetic couplings within the two adjacent magnetic centers bridged through oxalato, whereas dominant antiferromagnetic interaction was observed in the erbium compound of 6, respectively.